Seismic Efficiency and Seismic Moment for Small Craters on Mars Formed in the Layered Uppermost Crust - Rajšić, A.; Miljkovic, Katarina; Wójcicka, N.; Collins, G.S.; Garcia, R.F.; Bredemeyer, C.; Lagain, Anthony; Daubar, I.J.; Lognonné, P. (2023)
Seismic activity generated by impacts depends on impact conditions and properties of the impact site. Here, we combined mapping of the regolith thickness with numerical impact simulations to better estimate the seismic efficiency and seismic moment generated in small impact events in the uppermost crust on Mars. We used mapping of crater morphology to determine the regolith thickness that craters formed in. We found that local regolith thickness in the late Amazonian units is between 4 and 9 m. Combined with previous estimates for the NASA InSight landing site, we composed a more realistic uppermost crust analog and implemented it in numerical impact simulations. We estimated the seismic efficiency and seismic moment for small craters on Mars impacting a non-porous or fractured bedrock overlaid by 5, 10, or 15 m thick regolith. Seismic energy showed more dependence on target properties. Three orders of magnitude more energy were produced in stronger targets. The seismic moment does not depend on target properties, and we confirm that seismic moment is almost proportional to impact momentum. The resulting seismic moment is in agreement up to a factor of 4 between different target types. We improved the scaling relationships developed from numerical simulations used in seismic moment approximations by constraining its dependence on more realistic target properties.